FROM TEXT TO SCREEN: CELLULOID HELENS AND FEMALE STARDOM IN THE 1950s. (17th August 2015) - Nikoloutsos, Konstantinos P.
Abstract : This paper investigates the visual recreation of Helen in the medium of cinema by using as case studies two runaway productions of the 1950s: L'amante di Paride starring Hedy Lamarr and Helen of Troy with Rosanna Podestà in the title role. Examination of features such as costumes, makeup and hairstyle shows that in the former film Helen's representation is informed by and seeks to capitalize on Lamarr's status as a queen of glamour, equating Greek royalty with Hollywood royalty. The analysis of the second film explores further the homology between ancient and modern celebrity on screen and in extra-cinematic discourses, and shows how Podestà's stardom was built on and remained anchored in Helen's iconicity.